NANOGrav signal and LIGO-Virgo primordial black holes from the Higgs field. Issue 5 (1st May 2022) - Yi, Zhu; Zhu, Zong-Hong
Abstract: We show that the NANOGrav signal can come from the Higgs field with a noncanonical kinetic term in terms of the scalar induced gravitational waves. The scalar induced gravitational waves generated in our model are also detectable by space-based gravitational wave observatories. Primordial black holes with stellar masses that can explain LIGO-Virgo events are also produced. Therefore, the NANOGrav signal and the BHs in LIGO-Virgo events may both originate from the Higgs field.